Leadership: a tool for Organisational Empowerment in Nursing Education - Susan E van Niekerk (AOSIS, 1999)
Empowerment is the key ingredient in achieving the mission, vision and strategic direction of a nursing school. Opsomming Bemagtiging is die belangrikste faktor in die bereiking van die verpleegskool se missie, visie en strategiese bestemming. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.